Gender differences in dermatologist practice locations in the United States: A cross-sectional analysis of current gender gaps - Sepideh Ashrafzadeh, BS; Gregory A. Peters, MD; Elizabeth A. Buzney, MD; Hang Lee, PhD; Maryam M. Asgari, MD, MPH (Wolters Kluwer, 2021)
Background: The percentage of female dermatologists has increased from 6.9% in 1970 to 48.9% in 2017. Despite the changing gender composition of the dermatologist workforce, it is unknown whether there are gender-based differences in dermatology practice locations. Objective: This study aimed to characterize gender-based differences in dermatology practice locations across the United States. Methods: A cross-sectional study of all dermatologists in the 2020 Centers for Medicare and Medicaid Services Physician Compare Database was performed. The number of self-identified female dermatologists and total dermatologists in each county and state was tabulated, and Spearman's correlation coefficients between county-level demographic and socioeconomic characteristics and female practices were calculated. Results: Among 11,911 dermatologists, 5945 (49.9%) self-identified as female and 5966 (50.1%) as male. Of the 1052 counties with a dermatologist, 291 (27.7%) had no female dermatologist and 149 (14.2%) had no male dermatologist. The percentage of female dermatologists in each state ranged from 18.4% to 62.2%. Female dermatologists practiced more in areas with a higher percentage of democratic voters (r = +0.22) and higher median household income (r = +0.18), and less in rural counties (r = -0.18) or counties with higher uninsured rates (r = -0.11). Conclusion: Female dermatologists remain significantly underrepresented in some regions in the United States, particularly in the Mountain states and rural counties. As women continue entering the dermatologist workforce, these results can inform workforce planning strategies to improve the distribution and accessibility of dermatologists across the United States.